2020
DOI: 10.1007/s13394-020-00312-3
|View full text |Cite
|
Sign up to set email alerts
|

How are we progressing with academic numeracy at regional universities? Perspectives from first-year undergraduate studies

Abstract: This study provides an overview of the support provided for academic numeracy for first-year students across six Australian regional universities. Survey analysis of university academics provided an overview of the approaches used in academic numeracy in diverse cohorts. Further investigations via semi-structured interviews and secondary data were performed, providing details of the level of academic numeracy required in the subjects offered, identification of at-risk students and strategies for student suppor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
(16 reference statements)
1
5
0
Order By: Relevance
“…In making such comments they displayed a realisation of lacking areas of knowledge. Other studies have observed that factors contributing to poor progression are students' anxiety, lack of confidence with mathematics, and their lack of cognitive preparedness for tertiary mathematics study (Woolcott et al, 2020). Our findings align with the last point as knowledge gaps and apparent difficulties for some students with conceptual understanding and procedural fluency were evident in the student pilot cohort.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In making such comments they displayed a realisation of lacking areas of knowledge. Other studies have observed that factors contributing to poor progression are students' anxiety, lack of confidence with mathematics, and their lack of cognitive preparedness for tertiary mathematics study (Woolcott et al, 2020). Our findings align with the last point as knowledge gaps and apparent difficulties for some students with conceptual understanding and procedural fluency were evident in the student pilot cohort.…”
Section: Discussionsupporting
confidence: 87%
“…The deficiencies in mathematical skills of students entering university STEM programmes necessitates the provision of academic support, often delivered as mathematics bridging courses, support centres, peer to peer mentoring, mastery learning approaches, extracurricular mathematics courses or online resources (Groen et al, 2015;Galligan & Hobohm, 2015;Lake et al, 2017;Jackson & Johnson, 2013;Hillock et al, 2013;Matthews et al, 2013). These measures have often met with limited success as many students are unaware of their own deficiencies and participation rates are generally low (Matthews et al, 2013;Gallimore & Stewart, 2014;Mac an Bhaird et al, 2013;Patel & Rossiter 2011;Basitere & Ivala, 2015;Grehan et al, 2016;Woolcott et al, 2020).…”
Section: Mathematics Knowledge and Academic Progressionmentioning
confidence: 99%
“…Several factors can affect students' quantitative literacy and critical thinking. The results of the study showed that several factors influence quantitative literacy, namely interest in mathematics, motivation, length of study, numeracy habits, and curriculum while studying at senior high school (Garcia & Pintrinch, 1992;Mercader et al, 2018;ULM, 2020;Wong & Wong, 2019;Woolcott et al, 2019). In line with this, the ability to think critically is also influenced by several factors.…”
Section: Introductionmentioning
confidence: 80%
“…Evidence shows that it encompasses the environment setting of the flipped classroom which is concerned with the design of how it is conducted, the support which includes the instructors and pedagogy employed, and the instructional material used (Busebaia & John, 2020;Foldnes, 2016;Fredriksen, 2021;Shinaberger, 2017;Voigt et al, 2020). Conversely, studies reveal that the main elements that contribute to a meaningful intervention program in supporting at-risk students comprise participants of the program, a screening procedure to timely identify suitable participants for the program, instructional material prepared for the program, instruction during support sessions, an interventionist or instructor who delivers or facilitates the program, and on-going program monitoring for evaluation, reflection, and improvement (Björn et al, 2018;Büchele, 2020a;Fuchs et al, 2015;Heublein, 2014;Ketterlin-Geller et al, 2008;Lavy & Schlosser, 2005;Merritt, 2021;Özek, 2021;Woolcott et al, 2021). This article proposes a framework of FSC, particularly the implementation during class time for at-risk students as depicted in Figure 1, with the inclusion and adaptation of the key players for a flipped classroom and the main elements of a typical intervention program.…”
Section: A Flipped Support Classmentioning
confidence: 99%
“…In some cases, student support strategies that are designed to identify the risk factors of the at-risk students and follow up by a series of workshops has successfully resulted in a retention rate of 90% (Merritt, 2021). It has also been found that individual student support such as individualized assistance for low performers provided by instructors after the class increased the chances of program completion (Lavy & Schlosser, 2005), and may lead to improvement (Woolcott et al, 2021). Intervention for at-risk students that employs self-directed learning using workbooks and supported by facilitators during extra-curricular activity may have a greater impact on students with lower baseline scores in catching up, as compared to those with higher baseline scores (Maruyama & Kurosaki, 2021).…”
Section: Introductionmentioning
confidence: 99%